673 Utility of Diffusion Basis Spectrum Imaging in Quantifying Baseline Disease Severity and Prognosis of Cervical Spondylotic Myelopathy. (April 2023) - Zhang, Justin; Javeed, Saad; Greenberg, Jacob K.; Jayasekera, Dinal; Sun, Peng; Blum, Jacob; Dibble, Christopher; Song, Chunyu; Song, Sheng-Kwei; Ray, Wilson Zachary
Abstract : INTRODUCTION: Despite advancements in diffusion-weighted imaging, few studies have examined associations between diffusion MRI markers and CSM-specific clinical domains at baseline and long-term follow-up. METHODS: A single-center prospective cohort study enrolled fifty CSM patients who underwent surgical decompression and twenty controls from 2018-2020. At initial evaluation, all patients underwent diffusion-weighted MRI acquisition, followed by DTI and DBSI analyses. Diffusion-weighted MRI metrics assessed white matter integrity by fractional anisotropy, axial diffusivity, radial diffusivity, and fiber fraction. To improve estimations of intra-axonal anisotropic diffusion, DBSI measures intra-/extra-axonal fraction, and intra-axonal axial diffusivity. DBSI also evaluates extra-axonal isotropic diffusion by restricted and non-restricted fraction. Clinical assessments were performed at baseline and two-year follow-up and included the mJOA, SF-36 PCS, SF-36 MCS, NDI, MDI, and DASH. Pearson's correlation coefficients were computed to compare associations between DTI/DBSI and clinical measures. A False Discovery Rate correction was applied for multiple comparisons testing. RESULTS: At baseline presentation, of 36 correlations analyzed between DTI metrics and CSM clinical measures, only DTI fractional anisotropy showed a positive correlation with SF-36 PCS (r = 0.36, p = 0.02). In comparison, there were 30/81 (37%) significant correlations among DBSI and clinical measures. Increased DBSI axial diffusivity, intra-axonal axial diffusivity, intra-axonal fraction, restricted fraction, and extra-axonal anisotropic fraction were associated with worse clinical presentation (decreased mJOA, SF-36 PCS/MCS, and increased NDI, MDI, DASH). At latest follow-up, increased preoperative DBSI intra-axonal axial diffusivity and extra-axonal anisotropic fraction were significantly correlated with improved mJOA. CONCLUSIONS: Our findings demonstrate that DBSI measures may reflect baseline disease burden and long-term prognosis of CSM as compared to DTI. With further validation, DBSI may serve as a non-invasive biomarker following decompressive surgery.